Promoting peace or inciting violence? Explaining how decentralisation systematically affects the propensity of regional ethnic conflict - McArdle, Michele Panza (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Political Science, 2023)
This thesis investigates the varying effects of decentralisation on ethnic conflict. It seeks to offer a unified theory explaining why the outcomes of decentralisation reforms differ. More specifically it studies how these reforms affect the incentives of ethnic groups and in turn inter-group conflict. It employs a mixed-method approach focusing on multiple aspects of this topic. It consists of three empirical chapters. The first essay studies the relationship between decentralisation and ethnic conflict at the global level. The unified theoretical approach is developed in this chapter. It argues that there is competition between ethnic groups for state resources. Two mechanisms, private information and commitment problems, which are mediated by the ethnic make-up of the region explain why this primarily peaceful competition turns violent. A non-linear relationship between decentralisation and the propensity of ethnic conflict is hypothesised. Analysis of conflict in decentralised countries shows that conflict propensity is highest when there are two politically relevant groups and decreases for every subsequent group in a given region. The findings highlight the importance of the ethnic composition of sub-national regions in explaining the variation of violent conflict in decentralised nations. The second essay focuses on specific facet of the mechanism, namely the effect of decentralisation on institutional trust of ethnic groups. Loser's consent, which is based on an individuals trust in political institutions, is of central importance in keeping inter-ethnic conflict from turning violent. Specifically, the 2010 Kenyan decentralisation reforms are studied using survey data. It poses the research question: Does decentralisation, in an ethnically fractioned country, lead to an increase in trust in political institutions? The chapter distinguishes between four types of group status, depending on how an individual is affected by the decentralisation. The findings show that individuals which were members of national in-groups, but which found themselves in the out-group at regional level following decentralisation, had an increase in institutional trust. Otherwise decentralisation had a negative or no effect on trust. These results are somewhat counter-intuitive, has individuals who should have profited from such reforms did not see an increase in trust. The third essay seeks to refine the theoretical argument by analysing a special case of decentralisation, namely ethno-federalism. The defining aspect of ethno-federations is that regions are (in theory) ethnically homogenous, hence eliminating intra-regional ethnic conflict. However, ethnic conflict plays out at the national level between regional governments (representing respective ethnic groups). Focusing on a process-tracing case study of the outbreak of the Nigerian Civil War in 1967, the study shows that the institutionalisation of ethnic identities and rivalries, through an ethno-federal system lead to the development of a commitment problem. Due to historical rivalries, fostered by the institutional set-up, it was impossible for the warring parties to find a negotiated solution both prior to the civil war and during peace negotiations. A different institutional set-up, as implemented later in Nigeria, could have avoided such a conflict.
APPROVED
Keywords: Federalism; Decentralisation; Ethnic Conflict